(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Andrianov V. Е., Andrianov T. V. Culture healthy lifestyle as an important component of future teachers. The article substantiates the need to address the problem of educating students healthy lifestyle as animportant factor in the harmonious development of personality.